Pemeriksaan Cemaran Mikroba Susu Sapi Segar Daerah Limau Manis Tanjung Morawa Deli Serdang - Muhammad Gunawan; Suprianto (Yayasan Penelitian dan Inovasi Sumatera, 2024)
Background: Milk serves as a crucial source of human nutrition, particularly for infants who rely on it before they can digest solid foods. The mammary glands of female mammals produce it and is typically characterized by its pure white appearance. Objective: This study aimed to assess the levels of mesophilic aerobic bacteria and yeast mould present in fresh cow's milk obtained from farms in Limau Manis Tanjung Morawa. Methods: The investigation into contamination levels employed the Total Plate Count (TPC) method for aerobic bacteria and the Yeast Mold Count (YMC) method, both of which are based on the guidelines outlined in the Indonesian National Standard (SNI) No. 3141.1 of 2011. Results: Findings revealed that the levels of aerobic mesophilic bacteria, as determined by the TPC method, met the stipulated requirements of SNI No. 3141.1 of 2011 across all five farms surveyed. However, the research utilizing the YMC method indicated that the yeast mould counts in the milk from all five farms did not meet the established criteria. Conclusion: The analysis of microbial contamination using the TPC and YMC methods demonstrated compliance and non-compliance, respectively, with the standards outlined in SNI No. 3141.1 of 2011.